Labor productivity within the framework of the Labor Productivity and Employment Support national project - Zotikov, N. Z. (UPRAVLENIE / MANAGEMENT (Russia), 2024)
According to macroeconomic estimates, the Russian economy is characterized by a relatively low level of labor productivity, two to three times inferior to the economies of a number of industrialized countries. The lower level of labor productivity in Russia in comparison with the leading global economies is manifested especially at the microlevel. Increasing labor productivity is one of the most important tasks of the domestic economy in terms of ensuring competitiveness in the world markets. The importance of this process is intensified in the current conditions characterized by Western sanctions aimed at weakening the Russian economy. This determines the relevance of the present study .